2018
DOI: 10.1175/jcli-d-17-0147.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical–Extratropical Interactions Associated with East Asian Cold Air Outbreaks. Part II: Intraseasonal Variation

Abstract: Intraseasonal variations of East Asian cold air outbreaks (CAOs) in relation to the tropical atmosphere during 34 winters (DJF) are investigated. This study is a continuation of Part I, which discussed the interannual variability of East Asian CAOs. Two types of quantitative East Asian CAOs, western and eastern CAOs, are examined. Their variations are identified by the zonal integration of equatorward flux of cold air mass (CAM) below 280 K at 45°N over 90°–135°E and 135°E–180°. A day-lagged regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…The MJO‐related heating may modulate the extratropical circulations including cold surges. Simple general circulation models have been widely used to identify the circulation responses to prescribed tropical heating forces (Matthews et al, ; He et al, ; Guo et al, ; Abdillah et al, ). To estimate the circulation responses to heating anomalies associated with MJO‐C, we perform a numerical experiment using a simple baroclinic model with prescribed heating that is a mimic of precipitation‐induced latent heating (Figure a), and the results are shown in Figure S3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MJO‐related heating may modulate the extratropical circulations including cold surges. Simple general circulation models have been widely used to identify the circulation responses to prescribed tropical heating forces (Matthews et al, ; He et al, ; Guo et al, ; Abdillah et al, ). To estimate the circulation responses to heating anomalies associated with MJO‐C, we perform a numerical experiment using a simple baroclinic model with prescribed heating that is a mimic of precipitation‐induced latent heating (Figure a), and the results are shown in Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…The MJO-related heating may modulate the extratropical circulations including cold surges. Simple general circulation models have been widely used to identify the circulation responses to prescribed tropical heating forces (Matthews et al, 2004;He et al, 2011;Guo et al, 2015;Abdillah et al, 2017). To estimate the circulation responses to heating anomalies associated with MJO-C, The values in brackets indicate SDs between cases, and asterisk denotes statistically significant departures from climatology at the 95% confidence levels.…”
Section: Methodsmentioning
confidence: 99%
“…In the extratropics, the SAT has also a good relationship with ENSO through the signature of PCAM anomalies (Figures 2a and 2e). Previous studies showed that the increase or decrease in the PCAM amount indicates cooling or warming of the SAT, respectively (Abdillah et al, 2017(Abdillah et al, , 2018KA15;Shoji et al, 2014). Here we will quantify the robustness of their relationship.…”
Section: Relationship Between the Polar Cold Air Mass And Satmentioning
confidence: 97%
“…Previous studies reported that the distribution of the PCAM could be remotely controlled by variability in the tropics at both interannual (Abdillah et al, 2017;Kanno et al, 2017) and intraseasonal (Abdillah et al, 2018) time scales. The mechanisms appear to rely on the development of a poleward Rossby wave train excited by tropical convection anomalies (Hoskins & Karoly, 1981;Sardeshmukh & Hoskins, 1988;Trenberth et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation